Enhancing vaccine antibody responses by targeting Clec9A on dendritic cells. (December 2017) - Park, Hae-Young; Tan, Peck; Kavishna, Ranmali; Ker, Anna; Lu, Jinhua; Chan, Conrad; Hanson, Brendon; MacAry, Paul; Caminschi, Irina; Shortman, Ken; Alonso, Sylvie; Lahoud, Mireille
Abstract Targeting model antigens (Ags) to Clec9A on DC has been shown to induce, not only cytotoxic T cells, but also high levels of Ab. In fact, Ab responses against immunogenic Ag were effectively generated even in the absence of DC-activating adjuvants. Here we tested if targeting weakly immunogenic putative subunit vaccine Ags to Clec9A could enhance Ab responses to a level likely to be protective. The proposed "universal" influenza Ag, M2e and the enterovirus 71 Ag, SP70 were linked to anti-Clec9A Abs and injected into mice. Targeting these Ags to Clec9A greatly increased Ab titres. For optimal responses, a DC-activating adjuvant was required. For optimal responses, a boost injection was also needed, but the high Ab titres against the targeting construct blocked Clec9A-targeted boosting. Heterologous prime-boost strategies avoiding cross-reactivity between the priming and boosting targeting constructs overcame this limitation. In addition, targeting small amounts of Ag to Clec9A served as an efficient priming for a conventional boost with higher levels of untargeted Ag. Using this Clec9A-targeted priming, conventional boosting strategy, M2e immunisation protected mice from infection with lethal doses of influenza H1N1 virus. Vaccine technology: targeting the vaccine to the immune system Duration and intensity of vaccine response can be boosted using antibodies to target pathogen fragments to specific immune system cells. Dendritic cells exist to take fragments of infectious diseases and present them to the immune system, sparking host defenses. Now, researchers led by Monash University's Mireille Lahoud, and Ken Shortman of the Walter and Eliza Hall Institute, have successfully used antibodies to target fragments of influenza and hand, foot and mouth disease directly to dendritic cell molecules, specifically chosen to elicit a prolonged immune response. Mice inoculated with the targeted vaccine were protected from lethal influenza exposure, whereas the hand, foot and mouth disease vaccine elicited promising, but less marked results. With further development, this technology could provide a vital boost to vaccines that offer poor immunity on their own.